Dental Health Services Utilization and Associated Factors in Children 6 to 12 Years Old in a Low-Income Country - Carlo Eduardo Medina-Solis, DDS, MSc; Gerardo Maupomé, BDS, MSc, PhD; (Blackwell Synergy, 2008)
To determine the factors associated with the dental health services utilization among children ages 6 to 12 in León, Nicaragua.